Fabrication of Highly Conductive Porous Cellulose/PEDOT:PSS Nanocomposite Paper via Post-Treatment - Ko, Youngsang (Nanomaterials (Basel), 2019)
In this paper, we report the fabrication of highly conductive poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS)/cellulose nanofiber (CNF) nanocomposite paper with excellent flexibility through post-treatment with an organic solvent. The post-treated PEDOT:PSS/CNF porous nanocomposite papers showed a lower sulfur content, indicating the removal of residual PSS. The electrical conductivity of PEDOT:PSS/CNF porous nanocomposite paper was increased from 1.05 S/cm to 123.37 S/cm and 106.6 S/cm by post-treatment with dimethyl sulfoxide (DMSO) and ethylene glycol (EG), respectively. These values are outstanding in the development of electrically conductive CNF composites. Additionally, the highly conductive nanocomposite papers showed excellent bending stability during bending tests. Cyclic voltammetry (CV) showed a Faradaic redox reaction and non-Faradaic capacitance due to the redox activity of PEDOT:PSS and large surface area, respectively. Electrochemical energy storage ability was evaluated and results showed that capacitance improved after post-treatment. We believe that the highly conductive PEDOT:PSS/CNF porous nanocomposite papers with excellent flexibility described here are potential candidates for application in porous paper electrodes, flexible energy storage devices, and bioengineering sensors.